Inspiratory Muscle Training Improves Aerobic Capacity in Amateur Indoor Football Players - de Sousa, Matheus Martins; Pimentel, Matheus dos Santos; Sobreira, Isabela de Andrade; Barros, Rondineli de Jesus; Borghi-Silva, Audrey; Mazzoli-Rocha, Flavia (International Journal of Sports Medicine, 2020)
Inspiratory muscle training represents a recommended clinical practice to improve physical performance of healthy individuals, athletes, and those with chronic diseases. This study aimed to evaluate whether high- and low-intensity inspiratory muscle training interferes with the aerobic capacity of indoor soccer players. Volunteers were equally and randomly divided into CON (control group, no inspiratory muscle training); HIG (high-intensity group, inspiratory muscle training at 80% of maximal inspiratory pressure, 3 sets of 12 repetitions); and LIG (low-intensity group, inspiratory muscle training at 50% of maximal inspiratory pressure, 2 sets of 20 repetitions). Before and after inspiratory muscle training, maximal inspiratory and expiratory pressures, the incremental shuttle run test, and the 3-min step test were evaluated. Both inspiratory muscle training protocols improved maximal inspiratory and expiratory pressures, and indirect maximal oxygen consumption and distance traveled in the shuttle test compared to CON. However, only HIG achieved significant increases of indirect oxygen consumption and frequency of step rise in the 3-min step test (p<0.05). Inspiratory muscle training is an important tool to enhance maximal inspiratory pressure and exercise tolerance with potential benefits on submaximal aerobic capacity. However, high-intensity inspiratory muscle training improved aerobic capacity in amateur indoor soccer players in both submaximal tests.
Keywords: inspiratory muscle training; indoor football; aerobic performance; athlete; muscle training protocol